A New Method for Promoting Critical Thinking in Online Education - Al-Mubaid, Hisham (International Journal of Advanced Corporate Learning (iJAC), 2014)
The critical thinking process is a mental activity of actively and skillfully conceptualizing, applying, analyzing, synthesizing, and evaluating information to reach an answer or conclusion. It can also be viewed as a mental process that involves high quality and high level of thinking for problem solving and decision making. This paper presents and explains a new method for applying and promoting critical thinking for online education. The presented method can be applied in both online and regular classroom contexts, with being more practical and more appropriate for online education. The method consists of two components: an individual component and a team-based component. Each component includes a number of steps and the entire process is completed with a group setting. The Individual Component includes three steps: –List –Evaluate, and –Restructure; whereas the Team-based Component consists of three steps: –List, –Discuss and Evaluate, and –Integrate and Restructure. In each component, the learner is given essential opportunity to practice high level thinking and independent reasoning, and another chance to discuss and debate with other learners leading to an effective critical thinking medium. The method is straightforward to apply; and it guides students to practice and apply critical thinking to achieve quality learning and high level of understanding in the given learning task. This model has been applied and tested in both regular classroom setting and online education reaching satisfying and high levels of achieving critical thinking and intellectual growth among the learners.